La discrimination systémique sous la Charte québécoise. En marge des arrêts O'Malley et Bhinder - Lavergne, Guy (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
This note is a discussion of the various aspects of systemic discrimination in a comparative law perspective. The most important decisions and doctrinal opinions in American and Canadian law are considered and discussed. The issues considered are systemic discrimination, the BFOQ and business necessity defences, and the duty to accommodate. Recent developments in Canadian and American law are used as a framework to reevaluate the scope and meaning of the Quebec Charter with respect to issues of systemic discrimination.